2018
DOI: 10.17219/acem/84800
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of VEGF and bFGF in the course of propranolol therapy of infantile hemangioma in children: Are we closer to understand the mechanism of action of propranolol on hemangiomas?

Abstract: Background. Propranolol has become the treatment of choice for infantile hemangiomas (IH). Neither the pathogenesis of IH nor the mechanism of action of propranolol on them are well understood. Possible explanations include the inhibition of angiogenesis by decreasing vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF), induction of vascular endothelial cell apoptosis and vasoconstriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
3
15
1
Order By: Relevance
“…The detailed results were the subject of a previous publication. 6 The best therapeutic effect was obtained in the group of the youngest children, who started the treatment up to the 6 th month of life. The final therapeutic effect in the form of complete atrophy of the IH was noted in 69% of the children in this group.…”
Section: Resultsmentioning
confidence: 97%
“…The detailed results were the subject of a previous publication. 6 The best therapeutic effect was obtained in the group of the youngest children, who started the treatment up to the 6 th month of life. The final therapeutic effect in the form of complete atrophy of the IH was noted in 69% of the children in this group.…”
Section: Resultsmentioning
confidence: 97%
“…This finding is consistent with results from previous studies. Babiak-Choroszczak et al [22] showed significant decrease in vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF), and decreased blood flow in Doppler US during and after propranolol treatment. According to Shi et al [23], Doppler parameters including vascular density, blood flow velocity, and arterial peak systolic blood flow velocity significantly decreased in infantile heamangiomas after propranolol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed, including vasoconstriction, suppression of vascular endothelial growth factor and basic fibroblast growth factor with resulting inhibition of angiogenesis, inhibition of nitric oxide, and prevention of differentiation of stem cells within the IH into pericytes or endothelial cells. [71][72][73][74][75] Before initiating propranolol, a thorough medical history, family history, and physical examination should be completed. In the absence of concerns, baseline EKG and echocardiogram are not indicated.…”
Section: Treatmentmentioning
confidence: 99%